Klinické projevy experimentální autoimunitní uveitidy - Klímová, A; Seidler Štangová, P; Svozílková, P; Kučera, T; Heissigerová, J (Ceska a slovenska oftalmologie, 2016)
INTRODUCTION: Autoimmune uveitis is a sight threatening disease which in many cases fails to respond to conventional immunosuppressive or biological therapy. The research in experimental models of autoimmune uveitis helps to find new therapeutical strategies. The aim of this study is to present the clinical and histological signs of experimental autoimmune uveitis (EAU) in mice. METHODS: EAU was induced in C57BL/6 mice by subcutaneous application of IRBP (interphotoreceptor retinoid binding protein) in complete Freunds adjuvant and intraperitoneal application of pertussis toxin. Clinical evaluation of uveitis was performed in vivo using special imaging system with otoscope. Histological evaluation of uveitis was performed at day 35 post induction of EAU on hematoxylin and eosin stained frozen sections. Clinical and histological grading was used to assess the inflammation intensity of EAU. RESULTS: The intensity of inflammation is depicted on representative fundus images and histological images of retina at day 35 post induction. CONCLUSION: The model of EAU is robust and reproducible and allows us to study the immunopathological mechanisms of inflammation and its regulation. The inflammatory signs in our model are similar to findings of posterior uveitis of autoimmune etiology in humans, thus we may apply our experimental results in human medicine.
Keywords: myši inbrední C57BL; uveitida; autoimunitní nemoci; fundus oculi; modely nemocí na zvířatech; Eye Proteins; Retinol-Binding Proteins; Uveitis; Disease Models, Animal; Mice, Inbred C57BL; Retina; proteiny vázající retinol; imunosupresiva; zvířata; Autoimmune Diseases; Animals; oční proteiny; Immunosuppressive Agents; retina; Fundus Oculi